Mendelian Randomization Analysis Reveals a Causal Influence of Circulating Sclerostin Levels on Bone Mineral Density and Fractures. (2nd August 2019) - Zheng, Jie; Maerz, Winfried; Gergei, Ingrid; Kleber, Marcus; Drechsler, Christiane; Wanner, Christoph; Brandenburg, Vincent; Reppe, Sjur; Gautvik, Kaare M; Medina‐Gomez, Carolina; Shevroja, Enisa; Gilly, Arthur; et al.
ABSTRACT: In bone, sclerostin is mainly osteocyte‐derived and plays an important local role in adaptive responses to mechanical loading. Whether circulating levels of sclerostin also play a functional role is currently unclear, which we aimed to examine by two‐sample Mendelian randomization (MR). A genetic instrument for circulating sclerostin, derived from a genomewide association study (GWAS) meta‐analysis of serum sclerostin in 10, 584 European‐descent individuals, was examined in relation to femoral neck bone mineral density (BMD; n  = 32, 744) in GEFOS and estimated bone mineral density (eBMD) by heel ultrasound ( n  = 426, 824) and fracture risk ( n  = 426, 795) in UK Biobank. Our GWAS identified two novel serum sclerostin loci, B4GALNT3 (standard deviation [SD]) change in sclerostin per A allele (β = 0.20, p  = 4.6 × 10 −49 ) and GALNT1 (β  = 0.11 per G allele, p  = 4.4 × 10 −11 ). B4GALNT3 is an N‐acetyl‐galactosaminyltransferase, adding a terminal LacdiNAc disaccharide to target glycocoproteins, found to be predominantly expressed in kidney, whereas GALNT1 is an enzyme causing mucin‐type O‐linked glycosylation. Using these two single‐nucleotide polymorphisms (SNPs) as genetic instruments, MR revealed an inverse causal relationship between serum sclerostin and femoral neck BMD (β = –0.12, 95% confidence interval [CI] –0.20 to –0.05) and eBMD (β = –0.12, 95% CI –0.14 to –0.10), and a positive relationship with fracture risk (β = 0.11, 95% CI 0.01 to 0.21). Colocalization analysis demonstrated common genetic signals within the B4GALNT3 locus for higher sclerostin, lower eBMD, and greater B4GALNT3 expression in arterial tissue (probability >99%). Our findings suggest that higher sclerostin levels are causally related to lower BMD and greater fracture risk. Hence, strategies for reducing circulating sclerostin, for example by targeting glycosylation enzymes as suggested by our GWAS results, may prove valuable in treating osteoporosis. © 2019 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc.